COVID-19 confinement effects on game actions during competition restart in professional soccer players - García-Aliaga, A.; Marquina, M.; Román, I. R.; Solana, D. M.; Piñero Madrona, J. A.; del Campo, R. L.; Garrosa, F. N.; Mon-López, D. (International Journal of Environmental Research and Public Health, 2022)
The main objective of the present study was to compare high-intensity actions in a week of three matches before and after the COVID-19 lockdown. The observational methodology was used. This study analysed 551 professional soccer players from 22 different Spanish teams (LaLiga Smartbank 2019-2020) by a multi-camera tracking system and associated software (Mediacoach®, Spain). Variables of distances per minute and totals, travelled at High Intensity (HIR), Very High Intensity (VHIR), Sprint (HSR), player`s maximum speed, average speed, and the number of efforts in VHIR and HSR were analysed in the first and second half of the games, the full match, as well as in relation to the playing position. Players who participated in the same number of matches pre- and post-COVID-19 showed an increase in the total minutes played, p < 0.05, and small decreases in game actions, p < 0.05, with an effect size between 0.21 and 0.45, while players who participated in different number of matches pre- and post-COVID-19 showed a performance decrease, p < 0.05, with a size effect between 0.13 and 0.51; this was evident, particularly, for midfielders, p < 0.05, with a size effect between 0.39 and 0.75. The results seem to show that the playing intensity after COVID-19 confinement did not lead to large performance losses, except for midfielders who were the most involved players and showed a higher decrease in performance. The main findings of this study could provide insight to football coaches for rotations in starting line-ups and game substitutions, so as not to affect the intensity levels of the competitions.